The Murderous Act as a Response to Identity Crisis in Trifles - Sharma, Bam Dev (Bon Voyage, 2023)
Trifles is one of the revolutionary one act plays dealing with murder in which John Right is murdered by the wife, Minnie Right. She, however, refuses that she was fast asleep when the murder took place. The circumstances, however, evince that she is responsible for the murder. The play does not clearly manifest any such clues except the narrated accounts of other characters regarding her personality and her emotional and psychological. She behaves eccentrically when Mr. Hale, a close neighbor, comes to her house inquiring her husband, John Right. The investigation, then, takes place led by country attorney and other members. They enter the farm house, examining several rooms in course of investigation. On this story backdrop, this article tries to explore the cause of murder due to identity crisis. To make this claim justifi able, the research article is based on identity theory proposed by Peter Bourke, Castelles Manual, and David De Grazia.